2009
DOI: 10.1002/cbdv.200800158
|View full text |Cite
|
Sign up to set email alerts
|

Beauvericin Decreases Cell Viability of Wheat

Abstract: Recently, beauvericin (BEA) has been recognized as an important toxic compound synthesized by several Fusarium strains, infecting maize, wheat, and rice, worldwide. The effects of BEA on mammalian cells have been studied; however, its effects on the function of host plant cells are largely unknown. The purpose of our work was to assess whether BEA can affect the root and leaf cells of wheat cultivar (cv.) 'Arina' seedlings, using a cytotoxicity assay and fluorescence microscopy. Toxigenicity during wheat germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, studies on the synergistic interaction of co-occurring mycotoxins have demonstrated that mixtures of DON with EN B or BEA are more cytotoxic on mammalian cells than the DON toxin alone [ 30 ]. EN B is an emerging harmful toxin with impact on human and animal health as it can cause apoptosis and reduction of cell viability [ 31 ], while BEA is known to have toxic effects on germinating wheat [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, studies on the synergistic interaction of co-occurring mycotoxins have demonstrated that mixtures of DON with EN B or BEA are more cytotoxic on mammalian cells than the DON toxin alone [ 30 ]. EN B is an emerging harmful toxin with impact on human and animal health as it can cause apoptosis and reduction of cell viability [ 31 ], while BEA is known to have toxic effects on germinating wheat [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to its cytotoxicity, it has been employed in the treatment of malignant cells [6], as an antibacterial [7], antifungal [8], insecticidal, and nematocidal molecule [9]. The use of BEA for crop management has to be carefully evaluated because it can induce cell death and alteration of the antioxidant defense system in plants, such as the ascorbate-glutathione pathway [10,11]. This defense system is composed by enzymes such as the ascorbate peroxidase (APX, EC 1.11.1.11), the monodehydroascorbate reductase (MDHAR, EC 1.6.5.4), the dehydroascorbate reductase (DHAR, EC 1.8.5.1), and the glutathione reductase (GR, EC 1.6.4.2), and compounds, such as ascorbate (ASC), dehydroascorbate (DHA), reduced (GSH) and oxidized (GSSG) glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…BEA is a cyclic hexadepsipeptide produced by various phytopathogenic Fusarium species (Moretti et al 1995) with apoptotic properties (Ojcius et al 1991, Paciolla et al 2004) influencing membrane properties of root cells (Lemmens et al 1997, Pavlovkin et al 2006, Santini et al 2008, Šrobárová et al 2009). …”
Section: Discussionmentioning
confidence: 99%